HYDRAULIC FRACTURING DESIGN AND GROSS SPLIT ECONOMIC ANALYSIS USING FRACCADE FOR TIGHT OIL RESERVOIR: 10-YEAR PRODUCTION WELL FORECAST SIMULATION - Riki Darma; Doni Swadesi; Herianto Herianto; Suranto Suranto (Institut Teknologi Sepuluh Nopember, 2025)
This study evaluates the technical and economic feasibility of hydraulic fracturing in a tight oil reservoir using FracCADE simulation. A comparative analysis between fractured and unfractured wells was conducted, followed by a 10-year production forecast using decline curve analysis and an economic evaluation under Indonesia’s gross split contract scheme. The results demonstrate that optimized hydraulic fracturing significantly enhances well productivity and project economics, although financial performance remains sensitive to oil price and total production. The optimized HF design achieved a 237 ft fracture half-length and 1,064.5 mD·ft conductivity, with 98% slurry efficiency, anticipating a significantly reduced skin factor. The 10-year forecast projects an initial 300 BOPD for fractured wells, showing a productive decline, while unfractured wells are deemed economically unviable. Economically, the project demonstrates strong feasibility under gross split, with a contractor NPV of 18,563,527.11 USD (at 10% discount rate), an IRR of 28%, a PI of 1.52, and a POT of just 1.64 years. These findings highlight how optimal HF not only significantly boosts production but also ensures robust financial returns, despite sensitivity to production volume and oil price fluctuations.